SAT0039 Large tender joints have the greatest impact on longitudinal trajectories of function in early rheumatoid arthritis. (15th June 2017) - Lim, SHL; Schieir, O; Bartlett, S; Boire, G; Haraoui, B; Keystone, E; Tin, D; Thorne, C; Pope, J; Bykerk, V; Hitchon, C; ,
Abstract : Background: Physical function remains suboptimal in patients with early rheumatoid arthritis (ERA) despite adequate disease control. Hence, factors impacting function need further evaluation. Large weight bearing joints are more likely to impact overall function than small non-weight bearing joints although the magnitude of impact may be task dependent. By weighting large joints more than small joints, the Lansbury Articular Index (LAI) may have stronger associations with function than standard joint counts that give equal weight to small and large joints. Objectives: 1) To compare the correlations of weighted and non-weighted arthritis joint measures with physical function over time; and 2) to determine the impact of large compared to small joint involvement on the trajectory of HAQ in ERA. Methods: ERA participants had <1 year symptom duration at enrolment in a multicentre Early Arthritis Cohort and were followed prospectively. Arthritis activity measures (DAS28, tender 28 joint count (TJC28), swollen 28 joint count (SJC28), function (Health Assessment Questionnaire; HAQ) were captured at each visit. The LAI weighted 28 joint count (LT28) and swollen joint count (LS28) were calculated based on the standard 28 joint sites. Correlations of trajectories were calculated using joint modeling for each of the following: DAS28, TJC28, SJC28, LS28 LT28 with the HAQ (2 trajectories/model). Unadjusted effects of large joints (shoulders, elbows, hips knees, ankles) and hand joints (time-varying) on the HAQ trajectory were estimated with a series of generalized estimating equations (GEE). GEE models were adjusted for baseline age, sex and education. Results: ERA subjects (n=2125, 73% female; baseline mean (SD) age 53 (15) years, DAS28 5.1 (1.4)), were followed for median (IQR) 24 (10, 48) months. At their last visit 44% were in remission (DAS28<2.6). HAQ over time was highly correlated with the following: DAS28 (r=0.83), LT28 (r=0.83), and TJC28 (r=0.85) and moderately with the LS28 (r=0.59) and SJC28 (r=0.61) trajectories. Each increase in joint involvement was associated with increase in HAQ: large tender joint (0.110 (95% CI 0.102–0.116)); large swollen joint (0.109 (0.099–0.120)); tender hand joint (0.036 (0.032–0.039)); swollen hand joint (0.035 (0.032–0.039)). In multivariable modeling, after adjusting for age, sex, and education, large joints had greater effects (tender 0.074 (0.065–0.084), swollen 0.027 (0.014–0.04)) on HAQ than hand joints (tender 0.013 (0.009–0.017), swollen 0.008 (0.003–0.013)). Conclusions: Both Lansbury and standard joint count trajectories correlate similarily with HAQ in ERA. The weighting of large joints in LAI was insufficient to reflect the full impact of large joint involvement in ERA probably because HAQ questions emphasize large joint activities. The effects of large joint swelling may be under recognized due to difficulty in measuring hip, shoulder or elbow swelling. Overall, tender joints had a greater impact on function than swollen joints and large tender joints had the most impact on function. Disclosure of Interest: S. H. L. Lim: None declared, O. Schieir: None declared, S. Bartlett Consultant for: Pfizer UCB, G. Boire: None declared, B. Haraoui Grant/research support from: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Eli Lilly Janssen, Merck, Pfizer, Roche and UCB, Speakers bureau: Amgen, BMS Janssen, Pfizer and UCB, E. Keystone Grant/research support from: Abbott Laboratories, Amgen Inc, AstraZeneca Pharmaceuticals LP, Bristol-Myers Squibb, F.Hoffmann-La Roche Inc, Janssen Inc, Lilly Pharmaceuticals, Novartis Pharmaceuticals, Pfizer Pharmaceuticals, Sanofi-Aventis, UCB, Consultant for: Abbott Laboratories, AstraZeneca Pharma, Biotest, Bristol-Myers Squibb Company, Crescendo Bioscience, F Hoffmann-La Roche Inc, Genentech Inc, Janssen Inc, Lilly Pharmaceuticals, Merck, Pfizer Pharmaceuticals, UCB, Speakers bureau: Abbott Laboratories, AstraZeneca LP, Bristol-Myers Squibb Canada, F Hoffmann-La Roche Inc, Janssen Inc, Pfizer Pharmaceuticals, UCB, Amgen, D. Tin: None declared, C. Thorne Grant/research support from: AbbVie, Amgen, Celgene, CareBiodam, Lilly, Norvartis, Pfizer, Sanofi, UCB, Consultant for: AbbVie, Amgen, Celgene, Centocor, Genzyme, Hospira Janssen, Lilly, Medexus/Medac, Merck, Novartis, Pfizer, Sanofi, UCB, Speakers bureau: Medexus/MEdac, J. Pope Grant/research support from: Amgen, BMS, Pfizer, Roche, UCB, Consultant for: AbbVie, Actelion, Amgen, Bayer, BMS, Genzyme, Hospira, Lilly, Merck, Norvartis, Pfizer, Regeneron, Roche, Sandofi, UCB, V. Bykerk Shareholder of: Biogen (family), Consultant for: Abbvie, Pfizer, Genenech/Roche, Regeneron, BMS, UCB, Employee of: Biogen (family), C. Hitchon Grant/research support from: UCB